2021
DOI: 10.1177/21582440211010168
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Small-Scale Commercial Vegetable Farming Among Vegetable Growers in Nepal

Abstract: Various socio-economic factors play important roles in the adoption of commercial vegetable farming. Understanding these factors is crucial in enhancing the existing low rate of vegetable commercialization in Nepal, thereby achieving the overall development goal of poverty reduction. This article analyzes the personal, technical, and business factors associated with the adoption using Nepal Vegetable Crops Survey 2009–2010 data. A probit analysis is carried out. Caste/ethnicity is a critical factor hindering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Better market price has resulted in increased annual income, reduced indebtedness and purchase of household assets. This is in accordance with the study report of Joshi and Piya that personal factors associated to farmers are considered precursor factors that have a substantial impact on any farm household's decision-making process [12].…”
Section: Personal Factorssupporting
confidence: 91%
“…Better market price has resulted in increased annual income, reduced indebtedness and purchase of household assets. This is in accordance with the study report of Joshi and Piya that personal factors associated to farmers are considered precursor factors that have a substantial impact on any farm household's decision-making process [12].…”
Section: Personal Factorssupporting
confidence: 91%
“…The proactive measures were modeled with selective independent variables associated with socio-economic and demographic variations, i.e., diversity of household's livelihood options, wellbeing category, agricultural land owned, sex, number of adaptation activities employed, length of experiences in major occupation, and geographical variation of the dwellings to identify major determining factors. The independent variables were chosen by reviewing a wider range of pertinent literature, e.g., [73,103,109,[115][116][117][129][130][131][132][133][134], and consultation with local experts and community members while keeping in mind the local circumstances. In the context of Nepal, these variables hold great importance in addressing adaptation issues.…”
Section: Proactive and Reactive Adaptation: Concept And Analytical Fr...mentioning
confidence: 99%
“…Financial issues being the least severe, this shows that farmers have enough savings for capital investment. Though finance was not the limiting factor for the farmers in Dhangadhi to move forward with the commercial production of vegetables, various authors have identified financial limitation as the number one bottleneck of commercial farming, followed by inadequate market infrastructures such as market information systems, storage facilities, stable market price, and quality assurance services along with technical support services (Joshi and Piya, 2021;Kharel et al, 2021).…”
Section: Ranking Of Problems With Vegetable Productionmentioning
confidence: 99%
“…However, the vegetable production in the district has been constrained by various technological and socioeconomic factors, as elsewhere in Nepal. Joshi and Piya (2021) reported that various socio-economic factors such as caste, ethnicity, gender, family size, education level, land holdings, and income source are responsible for the adoption of commercial vegetable farming in Nepal. However, the specific information specific to this district and the region is scanty.…”
Section: Introductionmentioning
confidence: 99%